Answers

2015-01-29T22:11:12+08:00
You start by distributing the negative sign to the terms inside the parentheses.
2x - {3y - [5x - (7y - 6x) ] +1} = 2x - {3y - [5x - 7y + 6x ] +1}
Then distribute the negative sign to the terms inside the brackets
2x - {3y - [5x - 7y + 6x ] +1} = 2x - {3y - 5x + 7y - 6x +1} 
Finally, you distribute the negative sign to terms inside the curly brackets.
But I'll leave that to you. After doing that, you combine like terms and simplify.
0
2015-01-30T16:43:53+08:00
(7y-6x)
[5x-(7y-6x)] = 11x - 7y 
{3y-[5x-(7y-6x)+1} = 10y - 11x +1 
2x -{3y - [5x - (7y - 6x)] +1} = 13x -10y -1
0